2017
DOI: 10.1039/c7nr02534c
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature discrete-charge-fluctuation dynamics of a single molecule adsorbed on a carbon nanotube

Abstract: Detection and use of physical noise fluctuations in a signal provides significant advantages in the development of bio- and neuro-sensing and functional mimicking devices. Low-dimensional carbon nanomaterials are a good candidate for use in noise generation due to the high surface sensitivity of these materials, which may themselves serve as the main building blocks of these devices. Here, we demonstrate that the addition of a molecule with high redox activity to a carbon nanotube (CNT) field-effect transistor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In a previous work, we reported the generation of a spike signal from a device composed of a random and extremely dense network of single-walled carbon nanotubes (SWNTs) complexed with polyoxometalate (POM) [14]. It is known that the POM molecule displays a remarkable redox activity [15], which has been utilized as the source of fluctuations of electrical noise in molecular devices [16,17]. In addition to utilizing the stochastic fluctuation of the redox state, we proposed an abstract model of the network by assuming a two-dimensional (2D) structure of molecular junctions for the spike signal.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we reported the generation of a spike signal from a device composed of a random and extremely dense network of single-walled carbon nanotubes (SWNTs) complexed with polyoxometalate (POM) [14]. It is known that the POM molecule displays a remarkable redox activity [15], which has been utilized as the source of fluctuations of electrical noise in molecular devices [16,17]. In addition to utilizing the stochastic fluctuation of the redox state, we proposed an abstract model of the network by assuming a two-dimensional (2D) structure of molecular junctions for the spike signal.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was unclear what mechanism determined the timing of the current switch. The switching timing of several ten seconds could not be explained by the time constant of the active redox of the POM NPs 21,37) .…”
Section: Figure 3(a)mentioning
confidence: 91%
“…One approach for obtaining electrical nonlinearity Point contact current imaging atomic force microscopy (AFM) was used to measure the I-V curves, which showed nonlinear electrical properties as a result of the NPs behaving as nanodiodes on the single-wall nanotube (SWNT) wiring [17]. Another report suggested that a porphyrin single molecule can operate as a point local gate for individual SWNT FETs owing to the redox of a single molecule [18], which can be a source of telegraph noise of the system.…”
Section: Electric Nonlinearity Of Individual Cnt and Cnt Complexed Wi...mentioning
confidence: 99%